EMBRACING TECHNOLOGY: INSIGHTS INTO PRE-SERVICE PRIMARY TEACHERS’ VIEWS ON ICT IN ENGLISH EDUCATION - Isnaini Eddy Saputro; Dewi Sartika; Melisa Novianty (Language and Education Journal, 2025)
Information and Communication Technology (ICT) has become an essential component in modern education, particularly in language learning, due to its potential to enhance engagement, accessibility, and learner autonomy. This study investigates pre-service primary teachers’ perceptions of ICT in English language learning, focusing on four dimensions: attractiveness, perceived effectiveness, relevance, and motivation. Using a quantitative survey approach, data were collected through a structured questionnaire distributed via Google Forms to 26 Universitas Pendidikan Muhammadiyah Sorong students. Responses were analyzed using descriptive statistics based on a Likert scale. The results indicate that students perceive ICT as a beneficial and engaging tool in their language learning journey. Regarding attractiveness, 79% of respondents agreed that ICT enhances their English learning practices, and 78% acknowledged its usefulness in creating digital learning resources. However, 63% still valued traditional printed materials alongside digital tools. Regarding perceived effectiveness, 88% strongly agreed that ICT helps them learn new things, while over 70% affirmed its positive impact on grammar, vocabulary, pronunciation, and overall language proficiency. Furthermore, 82% of participants reported enjoying using technology in their learning process, and 77% indicated using ICT to communicate with peers from other countries, demonstrating its global learning potential. Additionally, 80% strongly desired to learn more about integrating ICT into classroom instruction. These findings highlight the significance of ICT in enhancing students’ motivation, engagement, and language skills. Therefore, integrating ICT effectively into English language instruction is crucial to support second-language acquisition in contemporary learning environments